IMPLEMENTASI MODEL PROBLEM BASED LEARNING TERINTEGRASI STEM UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS - Purnama, Rike Novianti; Rianti Cahyani; Nandang Arif Saefuloh (Uninus Journal of Mathematics Education and Science (UJMES), 2024)
The results of the 2015 PISA survey show that students' mathematical literacy in Indonesia is still low, in the field of mathematics it shows that Indonesia is ranked 62nd out of 72 countries. The problem of low mathematical literacy is caused by low interest in learning about the learning model used. This research aims to determine the increase in mathematical literacy skills through an integrated problem-based learning (PBL) model of Science, Technology, Engineering and Mathematics (STEM). The research method used was quasi experiment. The population in this research were two classes of students from class XI in one upper secondary school, in the even semester of the 2022/2023 academic year. The research results show that learning with the STEM integrated PBL model is able to improve students' mathematical literacy skills. This can be seen from the average N-Gain in the experimental class of 0.68 in the medium category, while the control class obtained an average N-Gain of 0.22 in the low category. The average N-Gain is supported by the results of the independent sample t-test hypothesis test, with a Sig (2-tailed) value of 0.00 < 0.05, meaning that the students' mathematical literacy abilities are significantly different from those in the control class.   Keywords: Problem Based Learning, Mathematical Literacy Ability , STEM